Post-regulation effect on factors driving environmental disclosures among Chinese listed firms - Yekini, Kemi C.; Adelopo, Ismail; Wang, Yan; Song, Surong (Emerald, 2018)
This study re-examines the factors that affect the level of Environmental Information Disclosures (EID) following the issuance of the “Environmental Information Disclosure Guidelines for Chinese Listed Companies”. The study is underpinned by stakeholder and legitimacy theories. Level of EID was measured for 100 Chinese companies using a scoring system and content analysis of their annual reports. The study explored the effect of ownership structure, managerial shareholding, economic power and industry classification on the level of EID using panel regression. The study revealed that with clearly spelt out guidelines, Chinese companies are prepared to disclose environmental information regardless of their economic power. We find that the overall level of EID in China remains lower when compared with developed economies. The findings are robust across several econometric models that sufficiently address various endogeneity problems. This paper contributes to the existing literature by using new and updated data to re-examine the factors that affect the level of EID among Chinese listed companies. The study is important and timely as it covers the period of 2014 - 2016 which is after the Chinese government strengthened the enforcement of EID. It highlights the effects of new regulations and underscored areas that still require government attention to foster effective environmental protection.